Searching for the Cause of the Gender Gap in Employment Losses during the COVID-19 Crisis - Jiyeon Kim (KDI Journal of Economic Policy, 2021)
The recession caused by the COVID-19 crisis has features that could disproportionately harm female employment. Risk of infection and social distancing measures may have disrupted jobs in face-to-face industries, which have traditionally hired more women than men. School closures and a consequent increase in childcare and homeschooling demands may have discouraged labor market participation by working mothers. Using the Economically Active Population Survey, I examine how female employment was affected by each factor. I find that the gender gap in the Employment to Nonparticipation (E to N) transition rates is twice as large as the gap in the Employment to Unemployment (E to U) transition rates. Women's overrepresentation in the face-to-face industries accounts for most of the gap in the E to U transition but only a third of the gap in the E to N transition. The rise in non-participation is especially pronounced among married women aged 39-44, the group most likely to have elementary-school-age children.
Keywords: E24; J2; J16; J21; J23; 330; COVID-19; Employment Losses; Gender Gap